The Dynamic Multiscale Nature of Climate Change Vulnerability: An Inuit Harvesting Example - Ford, J D; McDowell, G; Shirley, J; Pitre, M; Siewierski, R; Gough, W; Duerden, F; Pearce, T; Adams, P; Statham, S (Annals of the Association of American Geographers, 2013)
This article advances a vulnerability framework to understand how climatic risks and change are experienced and responded to by Inuit harvesters using a case study from Iqaluit, Nunavut. The article makes important contributions to methodological design in vulnerability studies, emphasizing the importance of longitudinal study design, real-time observations of human–environment interactions, community-based monitoring, and mixed methods. Fieldwork spanned five years, during which sixty-four semistructured interviews were conducted and historical records examined to develop an understanding of the processes and conditions affecting vulnerability. A local land use monitoring team was established, collecting 22,000 km of land use Global Positioning System (GPS) data and engaging in biweekly interviews (more than 100) on exposure, sensitivity, and adaptive capacity. This was complemented by analysis of instrumental data on sea ice and climate conditions. Results indicate that sea ice conditions are changing rapidly and affecting trail conditions, safety, and access to harvesting grounds. GPS data and biweekly interviews document real-time adaptations, with traditional knowledge and land-based skills, resource use flexibility, and mobility underpinning significant adaptability, including utilizing new areas, modifying trail routes, and taking advantage of an extended open water season. Sociospatial reorganization following resettlement in the 1950s and 1960s, however, has created dependency on external conditions, has reduced the flexibility of harvesting activities, and has affected knowledge systems. Within the context of these “slow” variables, current responses that are effective in moderating vulnerability could undermine adaptive capacity in the long term, representing overspecialized adaptations, creating the potential for further loss of response diversity and flexibility, and engendering potential downstream effects, creating trajectories of maladaptation. These findings challenge previous research that has argued that current resilience of the Inuit socioecological system is indicative of high adaptive capacity to future change and indicates that climate change might pose more serious risks to the harvesting sector than previously assumed.